2009
DOI: 10.1007/s11695-009-9924-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Adiponectin and Left Atrium Size in Uncomplicated Obese Patients: Adiponectin, a Link Between Fat and Heart

Abstract: A novel inverse relationship between adiponectin and LA size independent of age, sex, insulin resistance, and LV mass appears in our series. Adiponectin could be a link between adipose tissue and the heart, having an influence on cardiac remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
7
19
0
2
Order By: Relevance
“…Dyslipidemia prevalence (according to the ATP III guidelines) was low and similar in both groups [25] (Table 1). Glucose, insulin and HOMA-IR were significantly higher and adiponectin concentrations significantly lower in the morbidly obese group (P < 0.0005) in agreement with previous reports [23,24,26] ( Table 1). The triglycerides/HDL-cholesterol ratio, a surrogate marker of insulin resistance [27], was higher in the obese group, as reported previously [24].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Dyslipidemia prevalence (according to the ATP III guidelines) was low and similar in both groups [25] (Table 1). Glucose, insulin and HOMA-IR were significantly higher and adiponectin concentrations significantly lower in the morbidly obese group (P < 0.0005) in agreement with previous reports [23,24,26] ( Table 1). The triglycerides/HDL-cholesterol ratio, a surrogate marker of insulin resistance [27], was higher in the obese group, as reported previously [24].…”
Section: Discussionsupporting
confidence: 92%
“…The obese group displays increased systolic and diastolic blood pressure as well as heart rate compared with the NW group (P < 0.0005 for all) in agreement with previous reports [23,24,26] (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It has recently been shown that there is an inverse relationship between adiponectin, whose synthesis is downregulated in obesity, and left atrium size being a surrogate marker of left ventricle diastolic dysfunction and heart failure, linking adiposity to heart remodeling. 21 Contrary to an antihypertrophic effect of adiponectin, 22 resistin, an adipokine implicated in type II diabetes and insulin resistance, seems to promote heart hypertrophy in rodents. 23 In humans, the pathophysiological role of resistin has been questioned.…”
Section: Role Of Adipose Tissue In Cardiac Dysfunction C Look Et Almentioning
confidence: 99%